Tanggung Jawab PT. Lintas Kumala Abadi Dalam Kegiatan Pengangkutan Laut; Analisis Putusan Pengadilan Negeri Jakarta Barat No.642/PDT.G/2011/PN.JKT.BAR. - Muhammad Furqoni Ramadhan; Muhammad Yasir (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to explain the responsibilities of PT. Lintas Kumala Abadi and know the parties in the sea transportation agreement in terms of Law Number 17 of 2008 concerning Shipping and Commercial Law Book Article 307-747 in connection with a claim dispute between PT. Lintas Kumala Abadi and PT. Central Asia Insurance. This study uses normative juridical research by reviewing the laws and regulations, books and books related to this journal. There are three legal materials used in this study, namely primary legal materials, secondary legal materials, and non-legal materials. In this study, the author uses the decision of the West Jakarta District Court Number 642 / Pdt.G / 2011 / PN.Jkt.Bar namely a dispute between PT. Lintas Kumala Abadi as a carrier of goods owned by PT. Indofood Sukses Makmur (Defendant) against PT. Asuransi Central Asia as a guarantor for insured goods owned by PT. Indofood Sukses Makmur (Plaintiff). The results showed that the guarantor who has not paid compensation for the losses suffered by the insured cannot claim subrogation rights against third parties in this case the transporter. This was concluded from the consideration and decision of the judge on the decision of the West Jakarta District Court No. 642 / Pdt.G / 2011 / PN.Jkt.Bar.Keywords: Insurer, Insured and Subrogation